The Cratylus Testimony: Moving Toward Plato’s Ontology of the Human Body - Crowder, Jason Dale (University of the Witwatersrand, Johannesburg, 2024)
Socrates’ etymologies for the term σῶμα (human body) in the Cratylus 400b11-c9 excerpt raise a question that is often ignored or under-addressed in Platonic scholarship. That question is the focus of this dissertation. I aim to work out Plato’s definition and ontology of the human body as it unfolds and manifests within the Cratylus dialogue. My goal is to grasp what precisely Socrates’ σῶμα etymologies disclose about Plato’s ontological views toward the human body. Only a careful exegetical analysis of those etymologies can unveil such information. In other words, I want to know what the Cratylus 400b11-c9 testimony reveals about Plato’s ontological views concerning the human body. Hence, my research interest lies in three specific veins: (1) Socrates’ σῶμα etymologies in the Cratylus, (2) the relationship between a given etymology and a proper definition, and (3) the philosophical significance of these precise etymologies on Plato’s ontology regarding the human body. Much more entails each aspect than what appears initially. As the dissertation unfolds, other factors that need attention and require addressing will naturally arise. I propose that a careful and thorough exegetical analysis of the given σῶμα etymologies would reveal not only essential details for moving toward a proper understanding of Plato’s ontology of the human body but also proves that the Cratylus is a good entry point into this discussion itself. For such reasons, I shall argue that these etymologies are, in fact, instrumental in establishing the foundation of Plato’s overall ontological disposition of the σῶμα and, perhaps, Plato’s teleology of the human body too. Socrates’ σῶμα etymologies are not straightforward semantic connections but rather heavily influenced by a philosophical-religious perspective. As such, each seems relatively intelligible, and the statements are prima facie unproblematic at a precursory glance. While Plato’s character Socrates’ three σῶμα etymologies appear intelligible and prima facie unproblematic upon closer examination, that does not appear to be the case.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Arts in the field of Philosophy to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: Plato; Cratylus; Definition; Etymology; Forms; UCTD; SDG-4: Quality education